SAT0210 First-in-Patient Study of Namilumab, an Anti-GM-CSF Monoclonal Antibody, in Active Rheumatoid Arthritis: Results of the Priora Phase IB Study. (9th June 2015) - Huizinga, T.W.J.; Batalov, A.; Yablanski, K.; Stoilov, R.; Lloyd, E.; Wagner, T.; Saurigny, D.; Souberbielle, B.; Esfandiari, E.
Abstract : Background: Granulocyte macrophage-colony stimulating factor (GM-CSF) plays an important role in inflammation. Namilumab (AMG 203) is a neutralising human IgG1 anti-GM-CSF monoclonal antibody currently in development for the treatment of inflammatory diseases including rheumatoid arthritis (RA). Objectives: The primary objective was to investigate safety and tolerability of repeated subcutaneous injections of namilumab in patients with active RA. Signs of efficacy were investigated as an exploratory objective. Methods: PRIORA (NCT01317797 ) was a double-blind, placebo-controlled, randomised, dose-escalating phase Ib study in patients with mild-to-moderate RA on stable MTX doses for at least 12 weeks prior to randomisation. Patients received a total of 3 single injections of namilumab 150 or 300mg or matching placebo on Days 0, 15 and 29, with 12 weeks' follow-up. Results: A total of 24 patients were enrolled (70.8% female, mean age 55.9 years, mean baseline DAS28-ESR 4.7). Patients were randomised to namilumab 150mg (n=8), namilumab 300mg (n=7), or placebo (n=9). Namilumab was generally well tolerated and safety outcomes were consistent across treatment groups. A total of 49 treatment-emergent adverse events (TEAEs) were observed in 14 patients (58.3%) across the 3 groups. The percentage of patients with any TEAE was similar (namilumab 150mg: 62.5%; namilumab 300mg: 57.1%; placebo: 55.6%). Anti-namilumab antibodies were not detected. One patient on namilumab 150mg and 2 patients on placebo were excluded from the per-protocol post-hoc efficacy analysis due to major protocol violations related to not being on stable doses of corticosteroids and/or MTX prior to randomisation or receiving additional doses of corticosteroids and/or DMARDs during the study. In general, improvements in DAS28 scores (ESR and CRP) and joint counts were greater in the namilumab groups than placebo as early as Day 29. All 3 groups had moderate disease activity at baseline (mean DAS28-ESR: placebo =4.7; namilumab 150mg =4.9; namilumab 300mg =4.4). At Day 56 (4 weeks after the last study dose), more namilumab patients (10/14, 71.4%) had a DAS28-ESR response (>1.2 decrease from baseline) than placebo patients (2/7, 28.6%). The highest proportion of responders was in the namilumab 150mg group (6/7, 85.7%) compared with the namilumab 300mg group (4/7, 57.1%). No differences were observed across groups in DAS28-ESR response at 10 weeks after the last study dose. Conclusions: Namilumab was generally well tolerated in patients with active RA. The PRIORA results provide preliminary evidence of efficacy. This study supports further development of namilumab in patients with RA and potentially in those with other immune-related inflammatory diseases. Disclosure of Interest: T. Huizinga Grant/research support from: EU and Dutch Arthritis Foundation, Consultant for: Merck, UCB, Bristol-Myers Squibb, Biotest AG, Pfizer, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Nycomed, Boeringher, Takeda, and Eli Lilly, Employee of: Leiden University Medical Center, Speakers bureau: UCB, Bristol-Myers Squibb, Roche, A. Batalov: None declared, K. Yablanski: None declared, R. Stoilov: None declared, E. Lloyd Employee of: Takeda Pharmaceuticals International, T. Wagner Employee of: Takeda Pharmaceuticals International GmbH, D. Saurigny Shareholder of: Takeda Pharmaceuticals International, Employee of: Takeda Development Centre Europe Ltd., B. Souberbielle Shareholder of: Takeda Pharmaceuticals International, Employee of: Takeda Pharmaceuticals International, E. Esfandiari Shareholder of: Takeda Europe, Employee of: Takeda Europe